Synthesis and Bioactivities Study of Novel Pyridylpyrazol Amide Derivatives Containing Pyrimidine Motifs - Wu, Wenneng; Chen, Meihang; Fei, Qiang; Ge, Yonghui; Zhu, Yingying; Chen, Haijiang; Yang, Maofa; Ouyang, Guiping (Frontiers in Chemistry, 2020)
In this study, a series of novel pyridylpyrazol amide derivatives containing a pyrimidine moiety were synthesized and evaluated for their antifungal and insecticidal activities. Bioassay results indicated that some of the synthesized compounds exhibited good in vitro antifungal activities against Sclerotinia sclerotiorum, Phytophthora infestans, Thanatephorus cucumeris, Gibberella zeae, Fusarium oxysporum, Cytospora mandshurica, Botryosphaeria dothidea, and Phompsis sp. at 50 μg/mL, which were close to those of Kresoxim-methyl or Pyrimethanil. Meanwhile, bioassay results indicated that the synthesized compounds showed a certain insecticidal activities against Spodoptera litura, Mythimna separata, Pyrausta nubilalis, Tetranychus urticae, Rhopalosiphum maidis, and Nilaparvata lugens at 200 μg/mL, which were lower than those of Chlorantraniliprole. To the best of our knowledge, this study is the first report on the antifungal and insecticidal activities of pyridylpyrazol amide derivatives containing a pyrimidine moiety.